Additive impact of HER2‐/PTK6‐RNAi on interactions with HER3 or IGF‐1R leads to reduced breast cancer progression in vivo. Issue 1 (6th September 2014) - Falkenberg, Natalie; Anastasov, Nataša; Höfig, Ines; Bashkueva, Ksenia; Lindner, Katrin; Höfler, Heinz; Rosemann, Michael; Aubele, Michaela
Abstract : The human epidermal growth factor receptor 2 (HER2) and the protein tyrosine kinase 6 (PTK6) are often co‐ and over‐expressed in invasive breast cancers. At early diagnosis, only distinct groups, such as HER2‐or hormone receptor‐positive benefit from a targeted therapy. However, a part of these tumours develops resistance within a year of administration of the drug but the majority of the patients depends on general therapies with severe side effects. A PTK6‐directed approach does not yet exist. In our present study, we successfully demonstrate, in vitro and in vivo, a significantly additive reduction of tumourigenesis of breast cancer cells simultaneously depleted of both HER2 and PTK6. In comparison with single RNAi approaches, the combined RNAi (co‐RNAi) led to a stronger reduced phosphorylation of tumour‐promoting proteins. Moreover, the co‐RNAi additively decreased cell migration as well as two and three dimensional cell proliferation in vitro. The in vivo experiments showed an additive reduction (p < 0.00001) in the growth of xenografts due to the co‐RNAi compared with HER2 or PTK6 RNAi alone. Interestingly, the complexes of HER2 or PTK6 with tumour‐relevant interaction partners, such as HER3 or the insulin‐like growth factor receptor 1 (IGF‐1R), respectively, were also reduced in xenografts although their protein expression levels were not affected following the co‐RNAi of HER2 and PTK6. Our present study reveals the potential of using combined HER2‐ and PTK6‐ knockdown as a powerful strategy for the treatment of breast cancers. Therefore, the combined inhibition of these proteins may represent an attractive tool for efficient therapy of breast cancers. Highlights: co‐RNAi of HER2 and PTK6 additively inhibits 2D and 3D tumour cell proliferation. co‐RNAi of HER2 and PTK6 additively impairs in vivo tumour growth. RNAi of HER2 and/or PTK6 reduces complexes with tumour‐promoting proteins. co‐RNAi of HER2 and PTK6 is a powerful strategy for breast cancer therapy.